Allergic rhinitis and other comorbidities associated with asthma control in Thailand - Sriprasart, Thitiwat; Saiphoklang, Narongkorn; Kawamatawong, Theerasuk; Boonsawat, Watchara; Mitthamsiri, Wat; Chirakalwasan, Naricha; Chiewchalermsri, Chirawat; Athipongarporn, Athipat; Kamalaporn, Harutai; Kornthatchapong, Kumpol; Kulpraneet, Manaphol; Sompornrattanaphan, Mongkhon; et al. (Frontiers in Medicine, 2024)
Background: Asthma and allergic rhinitis (AR) can coexist and cause disabilities. This study aimed to assess the association between AR, asthma control, asthma-related quality of life, and other comorbidities.A cross-sectional study was conducted in adults with asthma in 6 hospitals in Thailand. The outcomes were association of asthma control assessed by the asthma control test (ACT), AR and asthma comorbidities. Not-well-controlled asthma was defined as ACT scores ≤ 22. The severity of AR was determined by visual analog scale (VAS). Severe AR was defined as VAS ≥5. Asthmarelated quality of life (AQLQ), comorbidities and total IgE were recorded.Results: A total of 682 asthmatic patients were included. Mean age was 55.1±14.3 years. 69.9% were female. Not-well-controlled asthma was present in 44.7%. The prevalence of AR was 86.1%. Moderate/severe persistent AR was diagnosed in 21.7% and severe AR was diagnosed in 30.2% of the patients. Inhaled corticosteroid-containing regimens were prescribed in 97.7% of patients. Intranasal corticosteroid and antihistamine were prescribed in 65.7% and 31.7%, respectively. Patients with not-well-controlled asthma had higher body mass index, VAS scores, proportions of pollution exposure, aeroallergen sensitization, severe AR, nasal polyp, urticaria, food allergy, gastroesophageal reflux disease, depression and anxiety, peptic ulcer, and asthma exacerbations, but younger age, lower AQLQ scores and lower FEV1. Correlation was found between AR severity and ACT (r=-0.461, p<0.001), AQLQ (r=-0.512, p<0.001), and total IgE (r=0.246, p<0.023).Conclusions: AR is prevalent in Thai asthmatic patients. AR severity is associated with asthma control and quality of life.